The mediating role of lecturer engagement in the relationship between human resource management, knowledge management, and higher education competitiveness - Anik Herminingsih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Higher education competitiveness depends on effective Human Resource Management (HRM) and Knowledge Management (KM), with lecturer engagement as a key element bridging the relationship between the two. Lecturer engagement emotionally and professionally drives teaching performance, research, and innovation, which contribute to institutional excellence. This study aims to explore the mediating role of lecturer engagement in enhancing university competitiveness. The purpose of this study is to explore and analyze the mediating role of lecturer engagement in the relationship between Human Resource Management (HRM), Knowledge Management (KM), and university competitiveness. This research uses the explanatory method with a quantitative approach to explain the relationship between variables through numerical data, focusing on competitiveness, human resources, knowledge management, and employee engagement. Conducted at a private college in Jakarta with B accreditation, the study included 187 respondents selected through proportional stratified random sampling to ensure accurate representation. The variables were measured using Likert scales, with each variable consisting of several dimensions and indicators to assess their influence on the competitiveness of the institution. Data were analyzed using SEM- AMOS. Result of this study indicated that human resource management has positive and significant effect on knowledge management, and competitiveness of higher education directly and through employee engagement as mediation variable. Knowledge management has positive and significant effect on employee engagement, but has a negative and significant effect directly on competitiveness of higher education institution. Lecturer engagement has positive and significant effect on competitiveness of higher education institution.